Comparação de vistorias para manutenção de edificações com o uso de plataforma elevatória e veículo aéreo não tripulado (VANT/DRONE) - Wendler, Izabelle Campa (2024)
In pursuit of agility and optimization in the use of material and human labor, the world has undergone various technological transformations. With this purpose, Remotely Piloted Aircraft (RPA), commonly known as Drones, has been utilized as a tool for obtaining aerophotogrammetric data in various engineering fields, including assisting in building inspections for the maintenance of hard-to-reach structures, providing safety and quality in reports and assessments. This study aims to analyze different techniques for conducting building inspections. To this end, the chosen research method was a comparative analysis between two surveys, one conducted through conventional inspection methodology, by using an elevated platform, and the other conducted using drone technology, allowing for a comparison of the results of the reports produced in both inspections. The fimdings demonstrate the feasibility and advantages of field inspections using drones. These advantages include a reduction in workplace accidents risks, more comprehensive inspection of identified issues, and higher quality in detecting and diagnosing anomalies and/or pathologies in the external structures and roofs of buildings.